Upconversion-mediated ZnFe2O4 nanoplatform for NIR-enhanced chemodynamic and photodynamic therapy. Issue 15 (14th March 2019) - Dong, Shuming; Xu, Jiating; Jia, Tao; Xu, Mengshu; Zhong, Chongna; Yang, Guixin; Li, Jiarong; Yang, Dan; He, Fei; Gai, Shili; Yang, Piaoping; Lin, Jun
Abstract : ZnFe2 O4, a semiconductor catalyst with high photocatalytic activity, is ultrasensitive to ultraviolet (UV) light and tumor H2 O2 for producing reactive oxygen species (ROS). Abstract : ZnFe2 O4, a semiconductor catalyst with high photocatalytic activity, is ultrasensitive to ultraviolet (UV) light and tumor H2 O2 for producing reactive oxygen species (ROS). Thereby, ZnFe2 O4 can be used for photodynamic therapy (PDT) from direct electron transfer and the newly defined chemodynamic therapy (CDT) from the Fenton reaction. However, UV light has confined applicability because of its high phototoxicity, low penetration, and speedy attenuation in the biotissue. Herein, an upconversion-mediated nanoplatform with a mesoporous ZnFe2 O4 shell was developed for near-infrared (NIR) light enhanced CDT and PDT. The nanoplatform (denoted as Y-UCSZ) was comprised of upconversion nanoparticles (UCNPs), silica shell, and mesoporous ZnFe2 O4 shell and was synthesized through a facile hydrothermal method. The UCNPs can efficiently transfer penetrable NIR photons to UV light, which can activate ZnFe2 O4 for producing singlet oxygen thus promoting the Fenton reaction for ROS generation. Besides, Y-UCSZ possesses enormous internal space, which is highly beneficial for housing DOX (doxorubicin, a chemotherapeutic agent) to realize chemotherapy. Moreover, the T 2 -weighted magnetic resonance imaging (MRI) effect from Fe 3+ and Gd 3+ ions in combination with the inherent upconversion luminescence (UCL) imaging and computed tomography (CT) from the UCNPs makes an all-in-one diagnosis and treatment system. Importantly, in vitro and in vivo assays authenticated excellent biocompatibility of the PEGylated Y-UCSZ (PEG/Y-UCSZ) and high anticancer effectiveness of the DOX loaded PEG/Y-UCSZ (PEG/Y-UCSZ&DOX), indicating its potential application in the cancer treatment field.